Analysis of the effectiveness of vaccination against COVID-19 based on real-world data in St. Petersburg - A. A. Kurylev; A. A. Zhuravkov; A. S. Kolbin (Izdatelstvo OKI, 2022)
Introduction. To date, 20 COVID-19 vaccines have been registered and used in the world, three of them have been developed in the Russian Federation. The results of clinical studies of the domestic vaccine «Sputnik V» were published in the international journal «The Lancet». However, there are not so many publications on the effectiveness of Russian vaccines in real practice, mainly from Argentina. At the beginning of August 2021, the Health Committee in St. Petersburg published data on the number of people who became ill with COVID-19 after vaccination in open sources. Aim. To evaluate the effectiveness of vaccination against COVID-19 based on real world data. Materials and methods. The data source was information on the number of persons, the number of persons vaccinated in St. Petersburg, as well as those who became ill after vaccination, as of 07/23/2021. Results. The risk of developing a new coronavirus infection among patients who have passed the full course (2 injections) of vaccination is 6.0-7.0 times lower (95 % CI: 6.34-7.24) compared with the group of patients who have not passed the full course (2 injections) of vaccination against COVID-19. Conclusions. Vaccination against COVID-19 is an effective way to reduce the risk of disease.